Relationships between ESG disclosure and economic growth: A critical review - Bertrand Kian Hassani; Yacoub Bahini (Journal of Risk and Financial Management, 2022)
The literature on the relationship between ESG disclosure and economic growth is relatively non-existent. Thus, this paper highlights the importance of taking this relationship into account in current sustainable policies. The main objective of extra-financial Disclosure is to mitigate Information Asymmetry. During this discussion, we show that ESG disclosure may not reduce information asymmetry as intended. We also show that complete extra-financial disclosure targeted by current policies is not optimal. There is an optimal disclosure threshold depending on the level of sustainable development of the country, the size of the companies and their development potential. Moreover, current ESG disclosure policies direct economies towards less polluting sectors, which is not necessarily optimal from an economic standpoint and could negatively affect economic activity and, therefore, the population's well-being. We also provide some policy implications and suggestions for future research on the ESG disclosure literature.
Keywords: Q01; O40; E02; O16; F64; G38; M14; 650; ESG; economic growth; greenwashing; sustainable investments; regulation